375. Performance Evaluation of RT-qPCR and RT-dPCR Platforms for the wastewater surveillance of SARS-CoV-2. (15th December 2022) - Choi, Hosoon; Coppin, John David; Chatterjee, Piyali; Xu, Jing; Mayo, Lynn; Brackens, Emma; Hwang, Munok; Bennett, Morgan; Gamage, Shantini D; Jinadatha, Chetan
Abstract: Background: The COVID-19 pandemic is an ongoing global health emergency. Wastewater-based epidemiology is a valuable tool for supplementing clinical testing in identifying infected individuals early thus containing disease transmission. To assess early detection of COVID-19, a building-level wastewater-based surveillance pilot project was implemented within VHA. Here, we report the results from 2 methods of polymerase chain reaction (PCR) testing of 1073 wastewater samples from VHA CLCs (i.e., nursing homes). Methods: Daily (Monday-Friday) wastewater samples were collected (January 11, 2021, to July 2, 2021) at eight CLCs located across the US and shipped overnight for processing. The samples were heat inactivated by incubating samples in a 65±1°C heating circulating water bath for 90 minutes. The virus in the wastewater was concentrated using InnovaPrep concentrating pipette select, and RNA was isolated from the concentrate and subjected to reverse transcription quantitative PCR (RT-qPCR) and RT-digital PCR. If SARS-CoV-2 was detected in the wastewater within the prior 10 days of a virus-positive occupant, the wastewater positivity was regarded as an early warning. Results: Twenty-seven positives and 7 inconclusive results were reported by RT-qPCR during the surveillance. Among the 27, 15 wastewater positives qualified as early warning and 12 positives were not verified by occupant positivity. Digital PCR with a cutoff value of 0.25 copies/uL of RNA for defining positivity had 28 positives qualifying as early warnings, and 115 positives were not verified by occupant positivity (Figure 1). Figure 1 Differences between RT-PCR and Digital PCR Positivity Conclusion: The overall viral loads of the wastewater samples were very low corresponding to the dip in cases seen in the US during the pilot period. Although sensitivity of digital PCR appears (based on 0.25 copies/uL of RNA for defining positivity) higher than that of RT-qPCR, there were more occurrences of unverified early warning that could impact precision. The cut-off selected for RT-digital PCR reported here is arbitrary and lacks industry consensus. More controlled studies are needed to determine sensitivity and precision as well as to standardize RT-digital PCR cutoffs to define positivity for routine use. Disclosures: Piyali Chatterjee, PhD, AHRQ Grant # 1R03HS027667-01: Grant/Research Support|AHRQ Grant # 1R03HS027667-01: Central Texas Veterans Health Care System Chetan Jinadatha, MD, MPH, AHRQ R01 Grant-5R01HS025598: Grant/Research Support|EOS Surfaces: Copper Coupons and materials for testing.